Sustainable Growth – Sustainable Financial Services in the European Union - Elekes, Andrea (Public Finance Quarterly, 2018)
Members of the European Union (in accordance with their international obligations) have committed themselves to sustainable development. The EU extends the (environmental, social and governance) sustainability criteria step by step to the already existing legal regulations and applies them automatically to new measures. One of the latest developments of this process is the draft regulation for sustainable financial services. Based on this draft regulation, only financial services covering sustainable economic activities may qualify as sustainable financial services (or green services). One of the most important objectives of the new regulation is to reflect economic activities that support sustainability and economic activities that have a negative impact on the environment (positive and negative externalities) in the prices of financial services. Governments can orient market actors in the direction of sustainability with the help of regulations concerning the financing of economic activities. The article therefore starts with economic growth theories, defines the concept of sustainable growth, then goes on to introduce the draft regulation on a sustainable approach to financial services published by the EU in 2018, and provides guidelines about how to identify economic activities that may qualify sustainable in the future, based on the draft regulation. Based on the new regulation, areas to which it is worth reallocating resources can be identified: improving resource efficiency; more compact (smarter), connected city systems; optimisation of land use; low-carbon infrastructure and energy systems, and innovation that boosts the development of these areas.